THE EFFECT OF FLY ASH UTILIZATION IN REINFORCEMENT CONCRETE: A REVIEW - Rachmat Hermawan; Rini Riastuti (Asosiasi Peneliti Sriwijaya, 2022)
Indonesia signed the Paris Agreement on facing climate change. Carbon dioxide is the main issue contributing to the greenhouse effect. Most power plant in Indonesia uses non-renewable energy to generate electricity. Increasing demand for electricity makes increasing coal consumption for steam power plants and directly contributes to greenhouse gasses from coal combustion and produces fly ash as a waste product. Otherwise, fly ash from Steam Power Plant is classified as pozzolanic materials being a part of substitution ordinary portland cement (OPC) on making reinforcement concrete. Many Researchers studied reinforcement concrete from fly ash composition and others development using renewable energy resources such as biomass. This paper presents a literature review on focus studying the properties of various types of fly ash and their effect on the performance of concrete, including corrosion resistance.